PENERAPAN CONTRAST BATH PADA PASIEN GAGAL JANTUNG KONGESTIF YANG MENGALAMI HIPERVOLEMIA DI RUANG TERATAI RUMAH SAKIT TK. II 03.05.01 DUSTIRA - Michelle Fitria Wawondatu, Meidy; Kusmawati, Dessi (Yayasan Putra Sukamanah Sejahtera, 2025)
Based on Riskesdas data in 2018, the prevalence of heart disease in Indonesia is around 1,017,290 population. Congestive heart failure is a condition in which the heart is unable to pump blood throughout the body properly. Signs of symptoms that usually appear are dyspnea and edema, where edema is a buildup of fluid or hypervolemia in several organs of the body. If not treated immediately can cause complications in the form of cardiogenic shock, thrombolytic episodes and pericardial effusion or cardiac tamponade. One of the non-pharmacological management that can be done to overcome hypervolemia is a contrast bath. Contrast bath is a treatment by soaking the feet in warm water, followed by cold water alternately. The temperature of the warm water used is 36,6 – 43,3 °C and the temperature of cold water is 10 - 20 °C. This case study aims to illustrate nursing care with the application of contrast bath in congestive heart failure patients who have hypervolemia. This type of case study method used a descriptive method with 1 patient with inclusion criteria for congestive heart failure patients who have lower extremity edema. The assessment showed that the patient felt tight and there was edema of the lower extremities, so that the nursing diagnosis that was established was hypervolemia with the implementation of the application of contrast bath carried out 3 times a day for 2 consecutive days with a time of 15 minutes once an action. The results of the case study of the application of contrast bath showed that there was a decrease in the degree of edema in both lower extremities which was originally at a degree of +3, to a degree of +2 after the intervention. It can be concluded that this contrast bath can overcome hypervolemia in congestive heart failure patients, the author also recommended to patients and families to perform this intervention independently.